A model of nongovernmental organization regulation with an application to Uganda - Burger, Ronelle; Dasgupta, Indraneel; Owens, Trudy (University of Chicago Press, 2015)
We develop a model of regulation of service-delivery nongovernmental organizations (NGOs), where future grants are conditional on prior spending of some minimal proportion of current revenue on direct project-related expenses. Such regulation induces some NGOs to increase current project spending but imposes wasteful costs of compliance verification on all NGOs. Under a large class of parametric configurations, we find that regulation increases total discounted project expenditure over a regime of no regulation, when verification costs constitute no more than 15% of initial revenue. We characterize the optimal regulatory policy under these configurations. We apply our analysis to a large sample of NGOs from Uganda and find regulation to be beneficial in that context.